UPAYA DIPLOMASI PUBLIK MALAYSIA TERHADAP INDONESIA DALAM MEMPROMOSIKAN PARIWISATA MEDIS TAHUN 2017-2022 - Fakhriyah Intan Maharani; Hendrini Renolafitri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Malaysia, as a country, tends to be the preferable option for Indonesians to get medical treatment due to its various benefits. The main factors that lead Malaysia as the chosen destination for Indonesian visitors are its popular image as a Muslim-friendly country, its geographical proximity, the quality of its service and facility, the affordability, the experience testimony, and the combination of tourism experience and medical treatment. Furthermore, in 2017, the Malaysia Healthcare Travel Council (MHTC) as the facilitator of the medical treatment industry targeted Indonesia to be one of its main markets to promote Medical Tourism effectively. This study analyses the perspective of pluralism on the nation-state level. As theoretical proof, this study uses the theory of public diplomacy and the concept of medical tourism. The data for this qualitative research was mainly done by gathering various data from books, journals, theses, official documents, reports, and websites that have relevance to the study. The result of the study has shown that Malaysia’s public diplomacy towards Indonesia was mainly done by promoting its medical tourism within 3 sectors: 1) news management, through social media and Healthcare Virtual Week Webinar; 2) strategic communication, through the Malaysia Healthcare Expo (MHX), held in several cities in Indonesia; 3) relationship building, by establishing the branch office of Malaysia Healthcare Travel Council in Jakarta and also partnership with flight agencies, health insurance, and banks in Indonesia. Keywords: Medical Tourism, Public Diplomacy, Indonesian Medical Tourists, Malaysia Healthcare Travel Council, Malaysia Healthcare Expo